Relationship between Socio-Demographic Factors and Adherence to Social Distancing Recommendations During Covid-19 Pandemic in Gonabad, Iran: A Cross-Sectional Study - Fatemeh Hadizadeh Talasaz; Ali Delshad Noghabi; Fatemeh Mohammadzadeh (Shiraz University of Medical Sciences, 2022)
Background: Adherence to social distancing recommendations provided by health authorities plays an important role in the prevention and control of COVID-19 transmission, regarding the lack of effective drug therapies. Therefore, this study aimed to identify the relationship between socio-demographic factors and adherence to social distancing recommendations during COVID-19 pandemic in Gonabad, Iran. Methods: In this cross-sectional study, 587 subjects aged 15 and older were selected using the convenience sampling method from urban and rural areas in Gonabad, Iran, from July to September 2020. Data were collected online using a socio-demographic characteristics form, the adherence to social distancing recommendations scale, and a coronavirus disease awareness survey. Subsequently, the obtained data were analyzed in SPSS software (version 16) using hierarchical linear regression. The statistical significance was considered as p <0.05. Results: 72.23% (95% confidence interval: 68.41%-75.82%) of the participants followed the recommendations of social distancing at the high level. Nevertheless, many differences were observed in the subgroups which resulted from the socio-demographic characteristics of the participants. According to the multiple linear regression model, sex (β=0.24, p <0.001) was the most important determinant of adherence to social behavioral recommendations, followed by occupation (β=0.15, p <0.001), age (β=0.14, P=0.007), awareness (β=0.13, P=0.001), and history of mental illness (β=-0.08, P=0.049). Conclusion: For the effective management of pandemics, the general public health policies should also consider the variability in responses and behavioral changes caused by socio-demographic characteristics, rather than focusing only on general measures, such as social distancing.